THE STORY MODEL OF THE HERO OF PREDESTINATION - Čechová, Mariana (Porównania, 2019)
The result of the analysis of folk types 461 and 930 (‘protected by fate’) is identification of their thematic-motivic intersections in the comparative framework of European and Asian literary tradition. At the same time, these intersections are valid inter-culturally. The research shows that an invariant semanteme of all studied myths, folk tales and legends is an unsuccessful attempt of a man of high social standing and power to kill his successor chosen by fate. The discussed ancient story motif also contains the famous Biblical motifs, such as the persecution of a child, heavenly omens and the fulfilment of prophecies.